Are nurses recognised, prepared and supported to teach nursing students: Mixed methods study. (July 2020) - Cusack, Lynette; Thornton, Karleen; Drioli-Phillips, Phoebe G.; Cockburn, Tina; Jones, Lisa; Whitehead, Michelle; Prior, Eleanor; Alderman, Jan
Abstract: Background: The requirement for clinical teaching and supervision of undergraduate nursing students is a continual high volume, high impact essential requirement of registered nursing staff. Nurses are integral in facilitating the learning of nursing students in the practice environment to deliver quality safe care. However nurses engaged in teaching and supervising nursing students have unique challenges. Objective: To understand how well recognised, prepared, and supported nurses perceive they are to teach and supervise undergraduate nursing students in the practice environment? Methods: Nurses from 12 different wards of two hospitals were invited to participate in the study. A sequential mixed methods approach comprising hard-copy questionnaires, completed by 59 nurses, and six focus groups. Four feedback sessions verified findings. Results: A low level of recognition and support for the amount of time available to nurses to teach and supervise was reported from both survey and focus group data. Four themes emerged from focus groups. Nurses recognised their role to teach and supervise students; The role in teaching and supervision was not recognised at a system level; Nurses could be more prepared to teach and supervise students; and Nurses required more support for their role in teaching and supervising students. A major challenge was the low level of support nurses perceived from the education sector in preparing students for placements. The nurses reported a disconnection of components of the student placement system, which was difficult to negotiate when undertaking this teaching and supervision role. Conclusion: The complex practice environment, where nursing student numbers are increasing and nurses have to navigate an often disconnected student placement system, requires a rethink of the precentorship or buddy one-to-one model of clinical placement. Addressing these challenges will be an essential step in protecting the interests of the public, nurses and nursing profession.